Aflatoxins biodetoxification strategies based on probiotic bacteria - Afshar, Parvaneh; Shokrzadeh, Mohammad; Raeisi, Shahram Naghizadeh; Ghorbani-HasanSaraei, Azade; Nasiraii, Leila Roozbeh (Toxicon (Oxford), 2020)
Aflatoxins are secondary metabolites of fungi that are the most dangerous mycotoxin and food safety challenges. Human exposure to mycotoxins occurs directly throughout the intake of contaminated agricultural products or indirectly throughout the consumption of products prepared with animal origin or obtained from animals that were fed with contaminated material. For detoxification and reducing threats to public health and the economic damage caused by the aflatoxins in animal and plants food products, different techniques (physical, chemical and biological) has been studied. All of these methods, by modifying and destroying the toxin molecular structure, would inhibit its transfer to the digestive system and could reduce the accessibility of toxins to the target tissue and eliminate it. In terms of the overarching challenges presented by the aflatoxins (AFs) contamination in foods and feeds, there is an urgent need to evolve cost-effective and appropriate strategies to combat this hazard. The review addresses have been noted the pathogenicity of AFs and the plausible mechanism of their-induced toxicity. Furthermore, assessed the AFs degradation using probiotic bacteria of their biological substance, and converting it into non-toxic or less toxic products, as a cost-effective and environmentally friendly strategy of detoxification method for providing appropriate solutions. •Aflatoxin B1 has a mutagenic, teratogenic, and carcinogenic effect on both human and animal organs.•One of the important food safety challenges is diagnosis and removal mycotoxins especially aflatoxins.•Probiotics in the viable and nonviable form are beneficial effects on human and animal health.•Probiotics are a safe, novel, and environment-friendly strategy for food hazards elimination.•Probiotics as a green policy for food safety can remove mycotoxins side effect through the biodegradation/bioabsorption mechanisms and gut protection.